Career Interventions at a Distance: A Systematic Literature Review - Célia Sampaio; Maria do Céu Taveira; Catarina Carvalho; Ana Daniela Silva (Societies)
Background: Due to global technological advances, psychology professionals have experienced constant changes in their daily routines. The field of career development and vocational psychology is no different. Amplified by the adjustments brought about by the circumstances of the pandemic, there has been an increased demand for and development of various distance intervention methodologies. Methods: This study presents a systematic review of distance career interventions, focusing on (1) rationale, (2) groups of the population, (3) structure, (4) evaluation, and (5) outcomes and recommendations. Eleven keywords, three databases, and five eligibility criteria were defined. Results: Sixteen articles were collected for analysis. The results showed a predominance of (1) career construction theory and social cognitive theory rationales, (2) a sample of university students, (3) group career intervention, (4) pre- and post-test evaluation systems, and (5) effects in different dimensions and recommendations about intervention research design. Conclusions: Although there has been an increase in the number of publications in recent years, few studies evaluate distance career interventions. There are also few studies with different target populations. In this sense, indications for future interventions and studies are given, as well as the implications of these studies for practice.